Stratigraphy of the north polar layered deposits of Mars from high‐resolution topography. Issue 8 (25th August 2016) - Becerra, Patricio; Byrne, Shane; Sori, Michael M.; Sutton, Sarah; Herkenhoff, Kenneth E.
Abstract: The stratigraphy of the layered deposits in the polar regions of Mars is theorized to contain a record of recent climate change linked to insolation changes driven by variations in the planet's orbital and rotational parameters. In order to confidently link stratigraphic signals to insolation periodicities, a description of the stratigraphy is required based on quantities that directly relate to intrinsic properties of the layers. We use stereo digital terrain models (DTMs) from the High Resolution Imaging Science Experiment to derive a characteristic of north polar layered deposit (NPLD) strata that can be correlated over large distances: the topographic protrusion of layers exposed in troughs, which is a proxy for the layers' resistance to erosion. Using a combination of image analysis and a signal‐matching algorithm to correlate continuous depth‐protrusion signals taken from DTMs at different locations, we construct a stratigraphic column that describes the upper ~500 m of at least 7% of the area of the NPLD and find accumulation rates that vary by factors of up to 2. We find that, when coupled with observations of exposed layers in images, the topographic expression of the strata is consistently continuous across large distances in the top 300–500 m of the NPLD, suggesting that it is better related to intrinsic layer properties than the brightness of exposed layers alone. Key Points: Layer protrusion from trough walls is a measurable property that characterizes layers Signal‐matching algorithms guided by manually matched layers can be used for stratigraphic correlation We present a stratigraphic column and relative accumulation rates for the upper 500 m of ~7% of the NPLD